1987
DOI: 10.1079/bjn19870027
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen balance studies in apparently healthy elderly people and those who are housebound

Abstract: 1. Metabolic balance studies (5 d) for nitrogen were carried out in twenty-four apparently healthy elderly people (age 69.7-85.6 years) and a heterogeneous group of twenty housebound elderly people (age 69.9-85.1 years) with chronic diseases. During the study all subjects ate self-selected diets, lived in their own homes and continued their normal daily activities. Seven of the housebound received meals-on-wheels 5 d/week.2. Healthy men and women had mean metabolizable energy intakes of 8.7 and 6.6 MJ/d respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
1

Year Published

1996
1996
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(24 citation statements)
references
References 26 publications
2
21
1
Order By: Relevance
“…However, there was a greater likelihood of frailty when two or more diseases were present than with any one. Conversely, the observation that a subset of those who were frail reported none of the diseases assessed supports the hypothesis that there may be two different pathways by which individuals become frail: one, a result of physiologic changes of aging that are not disease-based (e.g., aging-related sarcopenia [16] or anorexia of aging [30,31,49,50]), and the other a final common pathway of severe disease or comorbidity, as suggested by the higher Figure 1). These hypotheses remain to be confirmed.…”
Section: Discussionmentioning
confidence: 82%
“…However, there was a greater likelihood of frailty when two or more diseases were present than with any one. Conversely, the observation that a subset of those who were frail reported none of the diseases assessed supports the hypothesis that there may be two different pathways by which individuals become frail: one, a result of physiologic changes of aging that are not disease-based (e.g., aging-related sarcopenia [16] or anorexia of aging [30,31,49,50]), and the other a final common pathway of severe disease or comorbidity, as suggested by the higher Figure 1). These hypotheses remain to be confirmed.…”
Section: Discussionmentioning
confidence: 82%
“…Indeed, both arm muscle circumference and a 'nutritional index' score calculated from albumin, triceps skinfolds and transferrin levels were inversely correlated with protein intakes, implying no deleterious impact of consuming protein at the lower end of the observed range. Bunker et al (1987) reported actual N balances for housebound elderly men and women (n 20, 70-86 years) with a mean protein intake of 0·67 g protein/kg per d and mostly in negative balance, and also for healthy men and women (n 24, 70-86 years) with a mean protein intake of 0·97 g protein/kg per d at zero balance overall. However, there was no indication that protein intake determined N balance.…”
Section: The Elderlymentioning
confidence: 99%
“…Thus Munro concluded that the studies demonstrated no deleterious impact of consuming protein at the lower end of the observed range. Bunker et al (1987) reported actual nitrogen balances on both housebound elderly people ( n = 20), age 7&86 years, with mean daily protein intakes of 0.67 g protein/kg, and twenty-four healthy men and women, age 70-86, years with mean daily protein intakes of 0.97 g protein/kg. While the healthy group was in zero balance overall, the housebound group was in negative balance (see Fig.…”
Section: Implications F O R Protein Requirements From Population S T mentioning
confidence: 99%